School management system / Tan Swee Ling - Tan, Swee Ling (2002)
The purpose of this project is to develop a School Management System that utilized information technology to help to manage the school. As a school can be considered as an organization that was head by a principal, a well-managed school is important to make a school a conducive learning environment. School Management System is a client/server application that is develops mainly for secondary school. The aims of developing this system are to help the teachers manage resources and processes. It is also aims to reduce the workload of teachers by automating some of processes. This School Management System will be developing using Visual Basic and SQL Server 2000. It is hoped that this system will be beneficial to teachers as well as Students.